Characteristics of a firm's information environment and the information asymmetry between insiders and outsiders - Frankel, Richard; Li, Xu (Journal of Accounting and Economics, 2004)
We examine how financial statement informativeness, analyst following, and news relate to the information asymmetry between insiders and outsiders. Corporations’ timely disclosures of value relevant information and information collection by outsiders reduce information asymmetry, limiting insiders’ ability to trade profitably on private information. We use the profitability and intensity of insider trades to proxy for information asymmetry. We find that increased analyst following is associated with reduced profitability of insider trades and reduced insider purchases. Financial statement informativeness is negatively associated with the frequency of insider purchases. However, company news, good or bad, is positively associated with insider purchase frequency.